A high-efficiency composite desulfurizer and its preparation method
Through the combination of fulvic acid, maleic acid-acrylamide-acrylic acid copolymer and modified sodium alginate, a high-efficiency composite desulfurizer is formed, which solves the problem of insufficient system viscosity and high-temperature adaptability in wet hydrogen sulfide removal technology. , achieving efficient and low-cost high-temperature desulfurization effect.
Patent Information
- Application Number
- CN202411442995.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
In the existing wet hydrogen sulfide removal technology, it is necessary to reduce the gas temperature to improve the removal efficiency, but the use of macromolecular chelating agents leads to the system being viscous, reduces the desulfurization efficiency, and is difficult to adapt to high temperature conditions.
Combination of fulvic acid, maleic acid-acrylamide-acrylic acid copolymer, trimethylolamide aminomethane modified sodium alginate and soluble iron and copper salts is formed to form a high-efficiency composite desulfurization agent, and modified sodium alginate and copolymerization are carried out. The amide bonds in the substance reduce the viscosity of the system and adapt to high temperature conditions.
It achieves efficient removal of hydrogen sulfide gas at room temperature and high temperature, reduces the cost of desulfurization, avoids the problem of system viscosity, and is suitable for the high-temperature desulfurization needs of most manufacturers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer compositions and desulfurizing agents, in particular to a high-efficiency composite desulfurizing agent and a preparation method thereof. Background Art
[0002] Wet removal of hydrogen sulfide is a conventional method used in modern industry. It uses trivalent iron ions to react with hydrogen sulfide in the gas, oxidizes hydrogen sulfide into elemental sulfur, and converts trivalent iron ions into divalent iron ions. Wet removal of hydrogen sulfide has the advantages of simple process, non-toxicity, high working sulfur capacity, and no pollution, and is widely used. In the existing wet removal of hydrogen sulfide, it is generally necessary to reduce the temperature of the gas to be treated to room temperature. In this way, the enterprise needs special condensed water to reduce the temperature of the waste gas, which increases the cost of the enterprise to treat the waste gas.
[0003] In the wet process of removing hydrogen sulfide, iron ions need to be compounded with a chelating agent with a carboxyl group to form a chelate to improve the efficiency of removing hydrogen sulfide. Among them, the chelating agent with a carboxyl group can be EDTA, maleic acid, fulvic acid, iminodisuccinic acid, polymaleic acid, sodium alginate, etc. Usually, it is necessary to compound a small molecule chelating agent (such as EDTA) and a macromolecular chelating agent (such as polymaleic acid, sodium alginate) to improve the efficiency of removing hydrogen sulfide. However, the use of macromolecular chelating agents often causes the system to become viscous, which in turn reduces the desulfurization efficiency. For example, sodium alginate, a large number of carboxyl groups in it can react with water molecules to form an extremely viscous colloidal liquid. After polymaleic acid is dissolved, the solution also has a certain viscosity, which affects the use effect.
[0004] Therefore, in the field of industrial desulfurization, there is an urgent need to develop a composite desulfurizer with high desulfurization efficiency, which is suitable for high-temperature desulfurization of hydrogen sulfide gas, avoids system viscosity, and ensures the desulfurization effect of hydrogen sulfide. Summary of the invention
[0005] In order to solve the above problems, the object of the present invention is to provide a high-efficiency composite desulfurizing agent and a preparation method thereof.
[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0007] A high-efficiency composite desulfurizer is prepared by mixing fulvic acid, maleic acid-acrylamide-acrylic acid copolymer, tris(hydroxymethyl)aminomethane-modified sodium alginate, soluble iron salt and soluble copper salt in water.
[0008] The present invention also includes a method for preparing a high-efficiency composite desulfurizer, comprising the following steps:
[0009] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: by weight, 40 parts of sodium alginate are added to 2000-2500 parts of deionized water, the temperature is raised to 55-65°C, stirred for 30-40 minutes, cooled to 20-25°C, 12-13 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9-10 parts of N-hydroxysuccinimide are added thereto, stirred for 20-30 minutes, 10-14 parts of tris(hydroxymethyl)aminomethane are added to the obtained solution, the reaction solution is stirred at 20-25°C for 40-50 hours, the obtained mixed solution is dialyzed in deionized water for 3-4 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0010] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: add 25-35 parts of maleic acid and 240-250 parts of deionized water into a reactor, stir for 20-30 min, heat to 55-65° C., add 25-35 parts of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 115-125 parts of a mixed aqueous solution of acrylic acid and acrylamide in several portions, control the addition time to 1-2 hours, continue stirring for 2-4 hours after the addition is completed, and obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0011] ③ Take 40-60 parts of fulvic acid and add them to 3000-4000 parts of water, stir and dissolve, add 200-300 parts of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 20-30 parts of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 15-25 parts of soluble iron salt and 2-5 parts of soluble copper salt, stir and dissolve, adjust the pH value to 8.5-10.0 with alkali, and obtain a high-efficiency composite desulfurizer.
[0012] Preferably, the molecular weight of the sodium alginate is 80,000 to 120,000.
[0013] Preferably, the mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 0.5-2.5:2:14-20.
[0014] Preferably, the mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 7-10:10:35-75.
[0015] Preferably, the soluble iron salt is ferric chloride or ferric nitrate.
[0016] Preferably, the base is sodium carbonate or potassium carbonate.
[0017] Preferably, the soluble copper salt is copper nitrate or copper chloride.
[0018] The application of the high-efficiency composite desulfurizer of the present invention is used for removing hydrogen sulfide.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] The high-efficiency composite desulfurizer of the present invention can not only remove hydrogen sulfide gas at room temperature, but also can efficiently remove hydrogen sulfide gas at higher temperatures. The tail gas to be treated of the production enterprise does not need to be cooled for pretreatment, and can be directly desulfurized. The desulfurization efficiency is high, and the high-temperature desulfurization needs of most production enterprises can be met.
[0021] The high-efficiency composite desulfurizer of the present invention is prepared with fulvic acid, maleic acid-acrylamide-acrylic acid copolymer, and tris(hydroxymethyl)aminomethane modified sodium alginate as raw materials. Normally, the carboxyl group in sodium alginate will react with water molecules through hydrogen bonds to form extremely viscous substances. The present invention modifies sodium alginate with tris(hydroxymethyl)aminomethane, wherein a part of the carboxyl group is blocked, and an amide group is introduced, and the remaining carboxyl group in sodium alginate is more likely to form hydrogen bonds with the amide group, avoiding interaction with water, and effectively reducing the viscosity of the system. In addition, the present invention prepares copolymers by polymerization reaction of maleic acid, acrylamide, and acrylic acid, and an amide bond is also introduced in the molecular structure, and hydrogen bonds can be formed in the molecule to avoid system viscosity. Under the condition of increased temperature, the intramolecular hydrogen bond breaks, the molecular degree of freedom is higher, and the system viscosity is reduced instead, therefore, the desulfurizer of the present invention is suitable for use at room temperature and is also suitable for use under high temperature conditions. DETAILED DESCRIPTION
[0022] The object of the present invention is to provide a high-efficiency composite desulfurizing agent and a preparation method thereof. The present invention is further described below in conjunction with specific embodiments.
[0023] Example 1 A method for preparing a high-efficiency composite desulfurizer comprises the following steps:
[0024] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: 40 g of sodium alginate was added to 2000 g of deionized water, heated to 55° C., stirred for 40 min, cooled to 20° C., 13 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9 g of N-hydroxysuccinimide were added thereto, stirred for 20 min, 10 g of tris(hydroxymethyl)aminomethane was added to the resulting solution, the reaction solution was stirred at 20° C. for 50 hours, the resulting mixed solution was dialyzed in deionized water for 3 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0025] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: 25 g of maleic acid and 240 g of deionized water were added to a reactor, stirred for 20 min, heated to 55° C., 25 g of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 115 g of a mixed aqueous solution of acrylic acid and acrylamide were added thereto in several portions, the addition time was controlled within 2 hours, and stirring was continued for 4 hours after the addition was completed to obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0026] The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 2.5:2:20;
[0027] The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 10:10:35;
[0028] ③ Take 40g of fulvic acid and add it to 3000g of water, stir and dissolve, add 200g of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 20g of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 15g of ferric chloride and 2g of cupric chloride, stir and dissolve, adjust the pH value to 8.5 with potassium carbonate, and obtain a high-efficiency composite desulfurizer.
[0029] Example 2 A method for preparing a high-efficiency composite desulfurizer comprises the following steps:
[0030] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: 40 g of sodium alginate was added to 2500 g of deionized water, heated to 65° C., stirred for 30 min, cooled to 25° C., 13 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 10 g of N-hydroxysuccinimide were added thereto, stirred for 30 min, 14 g of tris(hydroxymethyl)aminomethane was added to the resulting solution, the reaction solution was stirred at 25° C. for 40 hours, the resulting mixed solution was dialyzed in deionized water for 4 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0031] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: 35 g of maleic acid and 250 g of deionized water were added to a reactor, stirred for 30 min, heated to 65°C, and 35 g of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 125 g of a mixed aqueous solution of acrylic acid and acrylamide were added thereto in several portions, the addition time was controlled within 1 hour, and stirring was continued for 2 hours after the addition was completed to obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0032] The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 0.5:2:20;
[0033] The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 7:10:75;
[0034] ③ Take 60g of fulvic acid and add it to 4000g of water, stir and dissolve, add 300g of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 30g of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 25g of ferric nitrate and 5g of copper nitrate, stir and dissolve, adjust the pH value to 10.0 with sodium carbonate, and obtain a high-efficiency composite desulfurizer.
[0035] Example 3 A method for preparing a high-efficiency composite desulfurizer comprises the following steps:
[0036] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: 40 g of sodium alginate with a molecular weight of 80,000 was added to 2100 g of deionized water, heated to 58°C, stirred for 32 min, cooled to 22°C, 12.2 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9.2 g of N-hydroxysuccinimide were added thereto, stirred for 22 min, 11 g of tris(hydroxymethyl)aminomethane was added to the resulting solution, the reaction solution was stirred at 22°C for 42 hours, the resulting mixed solution was dialyzed in deionized water for 3.5 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0037] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: 28 g of maleic acid and 242 g of deionized water were added to a reactor, stirred for 22 min, heated to 58° C., 26 g of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 118 g of a mixed aqueous solution of acrylic acid and acrylamide were added thereto in several portions, the addition time was controlled to be 1.5 hours, and stirring was continued for 2.5 hours after the addition was completed to obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0038] The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 1.5:2:15;
[0039] The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 9:10:55;
[0040] ③ Take 45g of fulvic acid and add it to 3200g of water, stir and dissolve, add 210g of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 22g of the tris(hydroxymethyl)aminomethane)-modified sodium alginate obtained in step ①, stir and dissolve, add 16g of ferric chloride and 3g of copper nitrate, stir and dissolve, adjust the pH value to 9.0 with potassium carbonate, and obtain a high-efficiency composite desulfurizer.
[0041] Example 4 A method for preparing a high-efficiency composite desulfurizer comprises the following steps:
[0042] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: 40 g of sodium alginate with a molecular weight of 120,000 was added to 2200 g of deionized water, heated to 60°C, stirred for 34 min, cooled to 24°C, 12.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9.5 g of N-hydroxysuccinimide were added thereto, stirred for 25 min, 13 g of tris(hydroxymethyl)aminomethane was added to the resulting solution, the reaction solution was stirred at 24°C for 45 hours, the resulting mixed solution was dialyzed in deionized water for 3.5 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0043] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: 32 g of maleic acid and 245 g of deionized water were added to a reactor, stirred for 25 min, heated to 62° C., 30 g of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 120 g of a mixed aqueous solution of acrylic acid and acrylamide were added thereto in several portions, the addition time was controlled to be 1.5 hours, and stirring was continued for 3.5 hours after the addition was completed to obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0044] The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 1:2:15;
[0045] The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 8:10:70;
[0046] ③ Take 55g of fulvic acid and add it to 3800g of water, stir and dissolve, add 260g of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 26g of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 24g of ferric chloride and 4g of cupric chloride, stir and dissolve, adjust the pH value to 9.5 with sodium carbonate, and obtain a high-efficiency composite desulfurizer.
[0047] Example 5 A method for preparing a high-efficiency composite desulfurizer comprises the following steps:
[0048] ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: 40 g of sodium alginate with a molecular weight of 100,000 was added to 2400 g of deionized water, heated to 62°C, stirred for 35 min, cooled to 24°C, 12.5 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9.5 g of N-hydroxysuccinimide were added thereto, stirred for 25 min, 13 g of tris(hydroxymethyl)aminomethane was added to the resulting solution, the reaction solution was stirred at 24°C for 45 hours, the resulting mixed solution was dialyzed in deionized water for 3.5 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate;
[0049] ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: 30 g of maleic acid and 246 g of deionized water were added to a reactor, stirred for 25 min, heated to 60° C., 30 g of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 120 g of a mixed aqueous solution of acrylic acid and acrylamide were added thereto in several portions, the addition time was controlled to be 1.5 hours, and stirring was continued for 3 hours after the addition was completed to obtain a maleic acid-acrylamide-acrylic acid copolymer solution;
[0050] The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 2:2:17;
[0051] The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 8:10:65;
[0052] ③ Take 50g of fulvic acid and add it to 3500g of water, stir and dissolve, add 250g of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 25g of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 20g of ferric nitrate and 3g of cupric chloride, stir and dissolve, adjust the pH value to 9.0 with potassium carbonate, and obtain a high-efficiency composite desulfurizer.
[0053] The high-efficiency composite desulfurizer obtained in Examples 1 to 5 is a wine-red liquid, which is miscible with water in any proportion, has a pH value between 8.5 and 10, and has a moderate pH value. Compared with the strong alkaline complex iron desulfurizer, the damage to the equipment is significantly reduced. The high-efficiency composite desulfurizer of the present invention is more suitable for removing hydrogen sulfide gas at high temperature.
[0054] 1. Test of minimum sulfur capacity of desulfurizer
[0055] Take 20 ml of the high-efficiency composite desulfurizer obtained in Examples 1 to 5, dilute to 200 ml (set the temperature to 25°C and 60°C for testing respectively) and place in a long-necked glass container, where the volume of the desulfurizer is at least two-fifths of the volume of the glass container, and add a concentration of 10 g / m 3Hydrogen sulfide gas is injected into the glass container at a rate of 100 ml / min through a gas distribution head placed at the bottom of the glass container. An opening is provided at the upper end of the glass container. The outlet hydrogen sulfide is detected by a hydrogen sulfide detector once a minute until hydrogen sulfide can be detected at the outlet. The ventilation time is recorded, and the minimum sulfur capacity is calculated by the following formula:
[0056] C min =10×v×T÷1000V;
[0057] C min is the minimum sulfur capacity,
[0058] v is the hydrogen sulfide flow rate, mL / min,
[0059] T is the ventilation time when hydrogen sulfide is detected, min
[0060] V is the volume of high-efficiency composite desulfurizer, mL;
[0061] The test results are shown in Table 1. The comparative example is the data obtained by using the preparation method of a high-activity complex iron desulfurizer of application number 202310727579.0.
[0062] Table 1 Minimum sulfur capacity test results
[0063]
[0064] It can be seen from the results in Table 1 that the minimum sulfur capacity of the high-efficiency composite desulfurizer of the present invention at room temperature is equivalent to the minimum sulfur capacity of the existing desulfurizer, but at high temperature, the minimum sulfur capacity of the high-efficiency composite desulfurizer of the present invention is reduced less, but the minimum sulfur capacity of the existing desulfurizer is reduced more, so the high-efficiency composite desulfurizer of the present invention is not only suitable for use at room temperature, but also suitable for use at high temperature. In practical applications, it is not necessary to reduce the temperature of the tail gas to be treated to room temperature for operation, which greatly reduces the desulfurization cost.
[0065] 2. Desulfurizer regeneration speed detection
[0066] Take the remaining liquid after measuring the minimum sulfur content of the desulfurizer and continue to introduce hydrogen sulfide. When the desulfurizer is completed and turns black, and the difference between the outlet hydrogen sulfide gas volume and the inlet hydrogen sulfide gas volume is within 10%, stop introducing hydrogen sulfide. Blow air directly into the solution with a blower until the amount of foam in the glass container decreases, the desulfurization liquid turns wine red, and large particles of sulfur appear in the container. At this time, the desulfurizer has been completely regenerated. Record the ventilation time. The results are shown in Table 2.
[0067] Table 2 Regeneration time of high-efficiency composite desulfurizer
[0068]
[0069] It can be seen from the results in Table 2 that the regeneration time of the high-efficiency composite desulfurizer of the present invention is short, and increasing the temperature can promote the regeneration rate and reduce the regeneration time of the desulfurizer. However, the desulfurizer of the comparative example has a long regeneration time because the viscosity of the system is too high due to the increase in temperature, which reduces the regeneration reaction rate.
[0070] 3. Actual use effect
[0071] The hydrogen sulfide content of a pharmaceutical factory is 10~12g / m 3 The production tail gas (without cooling treatment) is used as the gas source, and the processing gas volume is 50m 3 / h, the flow rate of the high-activity complex iron desulfurizer obtained by the present invention is 10L / h, the absorption and regeneration temperatures are both 45-55°C, and the desulfurization effect is shown in Table 3.
[0072] Table 3 Desulfurization effect table
[0073]
[0074] It can be seen from the results in Table 3 that the high-activity complex iron desulfurizer of the present invention has high desulfurization efficiency at 45-55°C, and the outlet accuracy is less than 10 mg / m 3 The tail gas in production can be desulfurized without cooling down, which can meet the desulfurization requirements of most production enterprises at high temperatures.
Claims
1. A high-efficiency composite desulfurizer, characterized in that: The alginate is prepared by mixing fulvic acid, maleic acid-acrylamide-acrylic acid copolymer, tris(hydroxymethyl)aminomethane-modified sodium alginate with soluble iron salt and soluble copper salt in water, and adjusting the pH value to 8.5-10.0 with alkali.
2. A method for preparing a high-efficiency composite desulfurizer, characterized in that: The following steps are involved: ① Preparation of tris(hydroxymethyl)aminomethane-modified sodium alginate: by weight, 40 parts of sodium alginate are added to 2000-2500 parts of deionized water, the temperature is raised to 55-65°C, stirred for 30-40 minutes, cooled to 20-25°C, 12-13 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 9-10 parts of N-hydroxysuccinimide are added thereto, stirred for 20-30 minutes, 10-14 parts of tris(hydroxymethyl)aminomethane are added to the obtained solution, the reaction solution is stirred at 20-25°C for 40-50 hours, the obtained mixed solution is dialyzed in deionized water for 3-4 days using a dialysis bag with a molecular weight of 3500, and lyophilized to obtain tris(hydroxymethyl)aminomethane-modified sodium alginate; ② Preparation of maleic acid-acrylamide-acrylic acid copolymer solution: add 25-35 parts of maleic acid and 240-250 parts of deionized water into a reactor, stir for 20-30 min, heat to 55-65° C., add 25-35 parts of a mixed aqueous solution of potassium persulfate and sodium bisulfite and 115-125 parts of a mixed aqueous solution of acrylic acid and acrylamide in several portions, control the addition time to 1-2 hours, continue stirring for 2-4 hours after the addition is completed, and obtain a maleic acid-acrylamide-acrylic acid copolymer solution; ③ Take 40-60 parts of fulvic acid and add them to 3000-4000 parts of water, stir and dissolve, add 200-300 parts of the maleic acid-acrylamide-acrylic acid copolymer solution obtained in step ② and 20-30 parts of the tris(hydroxymethyl)aminomethane-modified sodium alginate obtained in step ①, stir and dissolve, add 15-25 parts of soluble iron salt and 2-5 parts of soluble copper salt, stir and dissolve, adjust the pH value to 8.5-10.0 with alkali, and obtain a high-efficiency composite desulfurizer.
3. The method for preparing a high-efficiency composite desulfurizing agent according to claim 2, characterized in that: The molecular weight of the sodium alginate is 80,000 to 120,000.
4. The method for preparing a high-efficiency composite desulfurizing agent according to claim 2, characterized in that: The mass ratio of potassium persulfate, sodium bisulfite and deionized water in the mixed aqueous solution of potassium persulfate and sodium bisulfite is 0.5-2.5:2:14-20.
5. The method for preparing a high-efficiency composite desulfurizer according to claim 2, characterized in that: The mass ratio of acrylic acid, acrylamide and water in the mixed aqueous solution of acrylic acid and acrylamide is 7-10:10:35-75.
6. The method for preparing a high-efficiency composite desulfurizing agent according to claim 2, characterized in that: The soluble iron salt is ferric chloride or ferric nitrate.
7. The method for preparing a high-efficiency composite desulfurizing agent according to claim 2, characterized in that: The base is sodium carbonate or potassium carbonate.
8. The method for preparing a high-efficiency composite desulfurizing agent according to claim 2, characterized in that: The soluble copper salt is copper nitrate or copper chloride.
9. The use of a high-efficiency composite desulfurizer according to claim 1, characterized in that: Used to remove hydrogen sulfide.
Citation Information
Patent Citations
High-activity complex iron desulfurizer and preparation method thereof
CN116474532A
Preparation method of modified chitosan-sodium alginate composite flocculant, product of preparation method and application of product
CN109319908A
Complex iron desulfurizer
CN115337775A